Civic engagement and community service at research universities : engaging undergraduates for social justice, social change and responsible citizenship - Soria, Krista M.; Mitchell, Tania D., 1974- (London : Palgrave Macmillan, 2016)
Palgrave Studies in Global Citizenship Education and Democracy Series Editor: Jason Laker, San José State University, USA This book outlines how undergraduate students engage with civic and community projects and how this can be encouraged by their universities. It also explores how universities can build on this involvement and develop undergraduates' civic and democratic capacities, including programmatic strategies and conceptual frameworks for understanding the students' activities. As higher education across the globe experiences increasing student numbers it is important to understand how students engage with civic and community service.
PART III. ENGAGING UNDERGRADUATES FOR SOCIAL JUSTICE AND SOCIAL CHANGE: CRITICAL PERSPECTIVES ON STUDENTS' CIVIC ENGAGEMENT -- 11. Realizing a Critical Framework for Service-Learning at an American Public Research University / Douglas Barrera, Keali'i Troy Kukahiko, Lauren N. Willner, and Kathy O'Byrne -- 12. Student Activism as Civic Engagement: Challenging Institutional Conditions for Civic Leadership at University of Virginia / Walter F. Heinecke, Rose Cole, Ibby Han, and Nqobile Mthethwa -- 13. Seeking Social Justice: Undergraduates' Engagement in Social Change and Social Justice at American Research Universities / Tania D. Mitchell and Krista M. Soria -- 14. Revisiting the Civic Mission of the American Public Research University / Tania D. Mitchell.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 30, 2016).
Master record variable field(s) change: 072
Keywords: Citizenship -- Study and teaching (Higher); Social justice -- Study and teaching (Higher); Social change -- Study and teaching (Higher); Service learning -- Study and teaching (Higher); Undergraduates; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Citizenship -- Study and teaching (Higher); Service learning; Social change -- Study and teaching (Higher); Social justice -- Study and teaching (Higher); Undergraduates; Education; Higher Education; Social Work and Community Development; Sociology of Education; Electronic books